Cardiac mortality predictability of T-wave alternans in young ST-elevated myocardial infarction patients with preserved cardiac function - Mustafa Umut Somuncu; Huseyin Karakurt (KARE Publishing, 2019)
Objective: Primary prevention of sudden cardiac death in ST-elevation myocardial infarction (STEMI) is a complicated issue due to the highly heterogeneous population. The effect of T-wave alternans (TWA) on cardiac mortality has been examined in various populations, most often in patients with a high risk of fatal arrhythmia, such as patients with a low left ventricular ejection fraction (LVEF). The aim of the present study was to investigate the prevalence of TWA and its relationship to cardiac mortality in young STEMI patients with preserved LVEF. Methods: A total of 108 STEMI patients with preserved cardiac function who were under the age of 45 and underwent single-vessel primary percutaneous coronary intervention were enrolled in this prospective study. Preserved cardiac function was defined as an LVEF of ≥50% as detected with echocardiography 24 to 72 hours after the procedure. The TWA test was performed approximately 1 year after the STEMI occurrence. TWA positivity was defined with a maximal voltage of >64 μV and a heart rate of 125 beats per minute, as in previous studies. The patients were followed up for 5 years and overall cardiac mortality was measured. Results: There was a positive TWA finding in 24 patients (22.2%). There was no significant difference in the use of medications, traditional risk factors, or LVEF in those with TWA positivity. During a follow-up period of 5 years, 7 patients (6.5%) reached the endpoint. Patients with TWA positivity had 10.7 times greater odds for 5-year cardiac mortality, independent of other risk factors. Conclusion: Clinicians should consider using the TWA test in young STEMI patients, as TWA positivity may be associated with increased cardiac mortality in this population.